Dataset demonstrating physical properties of recycled wind turbine blade composites - Seyed Hossein Mamanpush; Hui Li; Karl Englund; Azadeh Tavousi Tabatabaei (Data in Brief, 2018)
Wind turbine blades that face end-of-life recycled mechanically. The recycled material was first comminuted via a hammer-mill through a range of varying screen sizes, resinated and compressed to a final thickness to manufacture second generation composites fabricated using recycled wind turbine material and a polyurethane adhesive. Physical properties (water sorption (WA), Thickness swelling (TS)) dataset of composites made from recycled wind turbine blades presented. Dataset also presented the influence of resin level, moisture content, mill screen size and density on the physical properties of composites.